Análisis de la dinámica de cambio de cobertura del suelo en áreas con plantaciones forestales comerciales en el municipio de Herveo (Tolima), durante el periodo 1986 - 2020 (2021)
he present work shows a multitemporal analysis between the years 1986 to 2020 from satellite images obtained from Landsat, identifying how the dynamics of commercial forest plantations have been in the village of Padua, Municipality of Herveo (Tolima) and determining the possible transformation scenarios of these areas destined for forest production, using as a category of analysis the georeferencing layers of areas registered by the Instituto Colombiano Agropecuario ICA in the area, for the recognition of the coverage in these areas, taking into account the classification Corine Land Cover established for Colombia. The free access software Qgis was used for image processing and obtaining the required results in the development of this project, processes such as supervised, cross classification and analysis of land cover change, were carried out through the Semi-Automatic Classification Plugin SCP.